Snap bean consumption in less developed countries - Janssen, W. (International Center for Tropical Agriculture, 1990)
Data on snap bean consumption are reviewed for Brazil, Colombia, Costa Rica, Indonesia, Philippines, Rwanda, Taiwan and Turkey to evaluate the present and possible future importance of snap beans in human diets, and the implication of consumption issues for snap bean research. Analyses of current consumption levels and their interaction with income, urbanization, prices and substitute vegetables are conducted. Price stability and market integration are also investigated. Snap bean quality preferences are described, including consumer attitudes to snap beans versus other vegetables. It is concluded that from a consumption point of view, snap beans are as worthy of research as any other vegetable. However, snap beans have the advantage of a complementarity with dry beans. (AS)